Efficient Ex Vivo Engineering and Expansion of Highly Purified Human Hematopoietic Stem and Progenitor Cell Populations for Gene Therapy - Zonari, Erika; Desantis, Giacomo; Petrillo, Carolina; Boccalatte, Francesco E.; Lidonnici, Maria Rosa; Kajaste-Rudnitski, Anna; Aiuti, Alessandro; Ferrari, Giuliana; Naldini, Luigi; Gentner, Bernhard (Stem cell reports, 2017)
Ex vivo gene therapy based on CD34+ hematopoietic stem cells (HSCs) has shown promising results in clinical trials, but genetic engineering to high levels and in large scale remains challenging. We devised a sorting strategy that captures more than 90% of HSC activity in less than 10% of mobilized peripheral blood (mPB) CD34+ cells, and modeled a transplantation protocol based on highly purified, genetically engineered HSCs co-infused with uncultured progenitor cells. Prostaglandin E2 stimulation allowed near-complete transduction of HSCs with lentiviral vectors during a culture time of less than 38 hr, mitigating the negative impact of standard culture on progenitor cell function. Exploiting the pyrimidoindole derivative UM171, we show that transduced mPB CD34+CD38− cells with repopulating potential could be expanded ex vivo. Implementing these findings in clinical gene therapy protocols will improve the efficacy, safety, and sustainability of gene therapy and generate new opportunities in the field of gene editing. •CD34+CD38− cells as an HSC-enriched starting population for ex vivo gene therapy•Reduced culture time (<38 hr) alleviates negative impact on progenitor cell potency•Prostaglandin E2 increases LV transduction up to 2× enabling shorter protocols•UM171 supports ex vivo expansion of mobilized peripheral blood HSCs In this article, Gentner and colleagues undertake a comprehensive strategy to advance ex vivo genetic engineering of HSCs for gene therapy. They experimentally define an optimal strategy to purify HSCs, which allows uncoupling long-term from short-term hematopoietic reconstitution, and implement ex vivo conditions that best preserve their biological properties applying novel transduction-enhancing compounds and pyrimidoindole derivatives to support HSC expansion.